(untitled) (Studia Archaeologica, 2025)
The Tuul River valley, one of Mongolia’s major river systems, has seen relatively little research on Paleolithic stone tool assemblages. As part of the "Stone Tool Sites in the Upper Tuul River Region" (2023–2024) project, a survey and excavation were conducted in 2024 at Uliin Tokhoi, with the objective of identifying new Paleolithic sites. Test excavations at three areas within the site yielded 100 lithic artifacts, while an additional 120 artifacts were surface-collected from 34 locations. Excavations revealed a primary artifact concentration between 0.8 m and 1.3 m below the surface, with no artifacts found beneath this stratigraphic layer. All artifacts exceeding 2 cm in length were systematically recorded. Sampling and fieldwalking surveys were the primary methods used for surface investigation. The lithic assemblage predominantly consists of blade-core reduction flakes, end scrapers, burins, knives, and perforators, characteristic of the Upper Paleolithic. Comparative analysis with dated sites in Mongolia and neighboring regions suggests that the site likely belongs to the Early and Initial Upper Paleolithic.